(untitled) (Strathmore Law Journal, 2025)
Social norms are strongly associated with pro-environmental behaviour, and social norm-based intervention is a popular strategy for promoting environmentally friendly behaviour. Recent body of knowledge has distinguished two types of social norms: injunctive norms (what most people should do or ought to do) and descriptive norms (what most group members do). However, Africa researchers in sub-Saharan Africa have scarcely investigated the dynamic relations of injunctive norms and descriptive norms with pro-environmental behaviour. We examined the contributions of descriptive norms and injunctive norms to pro-environmental behaviour in the sub-Saharan African context. Data was obtained from 581 students at a public university in Nigeria. They provided socio-demographic information and completed measures of social norms regarding negative emotional responses to climate change and sustainable consumption behaviours. Results showed descriptive norms were not a significant predictor of pro-environmental behaviour, but injunctive norm increase in injunctive norms was associated with reductions in pro-environmental behaviour. We also found a suppression effect (change of the original relationship), such that by itself, descriptive norms did not substantially predict pro-environmental behaviour but the inclusion of injunctive norms in the analytic model increased its positive association with pro-environmental behaviour. Similar suppressor effects were also found for the inverse association between injunctive norms and pro-environmental behaviour. This idea of mutual suppression suggests that social policies that promote pro-environmental behaviour due to shifts in descriptive norms will foster development in injunctive norms. Acknowledging this mutuality is informative for normative theory and can facilitate the efficient application of social norms as a tool for environmental behaviour policy.